Edukacyjna rola szkoły i nauczyciela wychowania fizycznego w kształtowaniu aktywności fizycznej młodzieŜy - Agnieszka Wartecka-Ważyńska, Agnieszka Wartecka-Ważyńska (Studia Edukacyjne, 2020)
Physical activity is an important element in psychophysical development of any human, including children and young people. Rational and regular participation in vigorous physical activity contributes to improvement and maintaining good health status. It also affects mood of a person and determines the quality of his or her life. The aim of the paper is to determine the role of school in the context of the factors that stimulate physical activity among young people at the age of 16 to 20 years. The paper has a literature-based and empirical character. The basic research methodologies adopted in the study included analysis of subject literature, diagnostic survey using questionnaire technique, and a statistical method. The questionnaire survey was carried out in 2012-2013 in secondary schools in the region of the Greater Poland Voivodeship in Poland in a group of 850 students. The study demonstrated that young people are physically active and participate in different forms of sport and recreation. However, one third of the young people studied spend their leisure time in a passive manner. They are not involved in any physical activity and spend their leisure time playing computer games, watching the TV, socializing, reading books and magazines and listening to the music. It should be noted that, in this context, the role of physical education teachers and school is critical.